Letter (copy) : 14th of April Fund - Tewson, Vincent
034-0017-001 International. HVT/AC/DT/921. 16th June, 1942. Mr. E. Elger, Scottish Trades Union Congress, 33, Elmbank Crescent, GLASGOW. Dear Mr. Elger, 14TH OF APRIL FUND. Thanks for your memorandum of 4th June in which you ask for particulars about the 14th of April Fund. We have been making enquiries, which are not yet completed, and as I find it may be a few days before I shall get the full story, I thought I had better let you have such information as we have. Shortly after we issued our list of Communist-led or Communist-controlled German, Austrian and Czechoslovak refugee organisations, the attention of our friends the I.F.T.U. was drawn by their Spanish colleagues to the Hogar Español, as being in the same category. We did not issue a further circular on this organisation because it had not attempted to make any contact with the British Trade Union Movement, and our action was justified because it has not been reported to us as having attempted to do so. I note that the 14th of April Fund operates from the same address as the Hogar Español, which establishes strong prima facie evidence that it is under the same leadership. We found, by the way, in our enquiries into the other refugee organisations referred to above that a feature of their administration was for them to have a common office in some cases. It may help to speed matters up if you can let me have a copy of the appeal which you have received. I will of course return it to you. I shall in any case be writing to you as soon as I have further information. Yours sincerely, Assistant Secretary. 292/946/34/17